Functional connectivity of the main intercalated nucleus of the mouse amygdala. - Mańko, M; Geracitano, R; Capogna, M (2011)
Intercalated cells (ITCs) of the amygdala are clusters of GABAergic cells that surround the basolateral complex of the amygdala (BLA). Growing evidence suggests that ITCs are required for the expression of fear extinction. The main intercalated nucleus (Im) is the largest of the ITC clusters and could also be important for emotional processing. We used whole-cell recordings from Im neurons in acute slices of mouse amygdala. We found that these neurons were medium-sized spiny projection cells. Their passive and active membrane responses were consistent with those previously reported in other ITC clusters. The axon of Im neurons was, in many cases, cut at the slice boundaries, suggesting long-range projections. Axonal branches could be detected in several amygdala nuclei where they made functional synapses. We also functionally studied Im cell inputs. Excitatory postsynaptic currents (eEPSCs) were evoked by the stimulation of the Im, intermediate capsula (IC), external capsula (EC) or BLA, when GABAergic transmission was pharmacologically blocked. An occlusion test indicated that fibres recruited by stimulating Im and IC, or Im and EC were distinct. These eEPSCs had both NMDA and AMPA receptor components. Inhibitory postsynaptic currents (eIPSCs) were evoked after the stimulation of the Im, the EC and the BLA, when glutamatergic transmission was pharmacologically blocked. Furthermore, dopamine reversibly hyperpolarised, and decreased the firing frequency and the input resistance of Im cells via dopamine type 1 receptor. Our data suggest that the Im is functionally connected to other amygdala nuclei and is under neuromodulatory influence. We propose that the Im serves as key neuronal substrate of fear extinction.